Homalonotidae Family (Trilobite) from Devonian of Malvinoxhosan Realm: species and systematic issues - Martins, Henrique B [UNESP]; Ghilardi, Renato P [UNESP] (Taylor & Francis, 2024)
Problems related to the classification of species are common in the field of palaeontology. The family Homalonotidae (Phacopida; Trilobites), in the Devonian period of the Malvinoxhosan Realm, can be included in this issue, since of its 22 species described since the 19th century, only half are considered valid today. This is mainly due to the existence of not very distinct diagnoses, the lack of comparisons between species and/or the lack of more up-to-date concepts. In order to demonstrate some of these problems and propose plausible solutions, this work was based on a bibliographic survey of the literature on the subject. The surveys showed the existence of 11 species of Homalonotidae, of the genera Burmeisteria, Burmeisterella, Digonus and Dipleura. The analyses indicated that some species were very similar (e.g. Burmeisteria accraensis and B. notica), while others had no distinguishable characteristics (e.g. Burmeisteria oiara). Thus, new analyses and classifications were proposed based on the specificity of each case and the use of more up-to-date concepts (e.g. taphotaxon), as well as the application of a phylogeny of morphological characters, in order to better understand the relationship between the taxa studied.